Silala basin dispute: Implications for the interpretation of the concept of international watercourse - Vučić Mihajlo (Anali Pravnog Fakulteta u Beogradu, 2017)
This article deals with the concept of the international watercourse and legal rules that regulate management of shared water resources. It is prompted by the current dispute before the International Court of Justice (ICJ) which raises the question of what is exactly the purpose of these rules and what should be the object of their protection. The interpretation of customary international law in this field points to the conclusion that even an artificially created international watercourse does not preclude the application of international law.